Clinical Characteristics and Pattern of Use of Topical and Oral Antifungal Drugs in Recalcitrant Dermatophytosis: A Hospital-Based Study - Parajuli, Sudip; Paudel, Upama (Journal of Institute of Medicine Nepal, 2025)
Introduction Studies on clinical characteristics of recalcitrant dermatophytosis from Nepal are sparse. The objective of this study was to characterize recalcitrant dermatophytosis clinically and to see pattern of use of existing antifungals drugs in these patients. Methods This was a prospective observational study carried out in department of dermatology, Tribhuvan University Teaching Hospital, Kathmandu, Nepal for a period of one year (December 2022 through November 2023). All the cases of recalcitrant dermatophytosis who visited dermatology outpatient department during this period were included in this study. The study variables included age, sex, occupation, site of involvement, prior use of topical drugs, oral terbinafine and oral itraconazole. Descriptive analysis of data was done using frequencies and percentages. Results Out of sixty cases of recalcitrant dermatophytosis, there were 32(53.3%) females and 28(46.7%) with mean age 34.47(SD +/- 11.96). Plaque (75%, n=45) presentation was the commonest type followed by annular (15%, n=9), polycyclic (6.7%, n=4), and patch type (3.3%, n=2). Multiple sites were involved in 35 patients (58.3%). Most of the patients had used topical corticosteroids (36.7%, n=22) at presentation. Sixteen patients had history of use of oral drugs prior to presentation without any improvement; Itraconazole (23.3%, n=14) was the most common drug used, followed by Terbinafine (1.7%, n=1). Conclusion: Plaque type of recalcitrant dermatophytosis in young female with multiple sites of involvement was the most common presentation. Many patients had used topical corticosteroid and topical antifungals while majority had never used oral drugs prior to presentation in hospital.